The impact of Fintech on Islamic banking and the collaboration model: a systematic review studies in Indonesia - Idah Zuhroh (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
The Fintech company has raised its number significantly in Indonesia and threatened the banking sector as Islamic Banking is not the exception. Fintech can provide better financial services than Islamic Bank with its technological advantages. This research aims to observe the effect of Fintech's on Islamic banks and discover the collaboration model between Fintech and Islamic banks to improve financial services. The method was carried out by Systematic Literature Review (SLR), then analyzed using Nvivo 12 to quantify the words counted to the papers found. The result showed that there were 14 papers found to analyze in the systematic review. According to Nvivo 12 words counted result, the highest words counted was ‘services’ with 21%, followed by ‘user’ and ‘customers’ combined with 16%. Furthermore, Fintech acts as the disruptor for Islamic Banking, shown in its Return on Asset and its potential to take over the millennial customers segment. The collaboration can be done by sharing product marketing, loans, and transaction services. For the customer, big data analysis, the legal aspects, risk of human error, and data security protocol should be mitigated by tightening the registration system to minimize fraud, enhancing the internet server to prevent failure transactions, and closely cooperating with the Authority of Financial Service in Indonesia (OJK) to ensure the legal aspects are fulfilled.